CARA BERTAHAN HIDUP PENYANDANG DISABILITAS DI KOTA DUMAI - Ramadhani, Cut Fitri; ", Jonyanis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This thesis analyzes the factors that influence persons with disabilities to maintain their lives. How to survive is very influential on how to adapt living things to their environment, because adaptation to the environment is very influential on human behavior so that the desired goals are achieved. This way of adapting covers almost all human behavior in daily life.The researchers' findings show that the factors that influence people with disabilities work are socioeconomic conditions and physical conditions. Besides that, to survive people with disabilities in Dumai City also utilize social networks by building relationships with people from relevant agencies who always provide assistance.According to the definition given by the World Health Organization (WHO), disability is a limitation or lack of ability of an organ so that it affects the physical or mental ability to display activities according to the rules or still within normal limits. The main social problem faced by people with disabilities "disability" is that they are abnormal in a level so clear that others do not feel good or are unable to interact with it. The issue of people with disabilities or people with different abilities is the problem that most rarely gets the attention of the government and the community. Keywords: Survival strategies for persons with disanilities